Perlindungan Hukum Terhadap Pejuang Lingkungan Hidup Dalam Mewujudkan Lingkungan Hidup Yang Baik Dan Sehat - Puspitasari, Dinarjati Eka (UI Scholars Hub, 2022)
The right of environmental defenders not to be sued civilly or prosecuted criminally is part of human rights regulated in Article 66 of Law 32/2009 (UUPPLH), known as Anti Strategic Lawsuit Against Public Participation (Anti-SLAPP). But in practice, the law is used as a tool to curb public participation. In this case, environmental organizations have an important role to play in assisting communities in fighting for their environmental rights, ranging from non-judicial mechanisms to becoming amicus curiae in court. This research examines literature sources with a library research method through a statutory approach, case approach, and conceptual approach. The result indicates that although Law No. 32/2009 provides legal protection to fight for the right to a good and healthy environment, the community is still prosecuted when fighting for the right to the environment, either through a lawsuit or criminalized. In conclusion, the Anti-SLAPP regulation in Indonesia is still relatively weak in providing justice, benefits, and legal certainty for environmental fighters in Indonesia.